Repeated resection for recurrent intrahepatic cholangiocarcinoma: A retrospective German multicentre study - Bartsch, Fabian; Eberhard, Johannes; Rückert, Felix; Schmelzle, Moritz; Lehwald-Tywuschik, Nadja; Fichtner-Feigl, Stefan; Gaedcke, Jochen; Oldhafer, Karl J.; Oldhafer, Felix; Diener, Markus K.; Mehrabi, Arianeb; Settmacher, Utz; et al. (Liver international, 2021)
Background Tumour recurrence is common after resection of intrahepatic cholangiocarcinoma (ICC). Repeated resection is a potential curative treatment, but outcomes are not well-defined thus far. The aim of this retrospective multicentre cohort study was to show the feasibility and survival of repeated resection of ICC recurrence. Methods Data were collected from 18 German hepato-pancreatico-biliary centres for patients who underwent repeated exploration of recurrent ICC between January 2008 and December 2017. Primary end points were overall (OS) and recurrence-free survival from the day of primary and repeated resection. Results Of 156 patients who underwent repeated exploration for recurrent ICC, 113 underwent re-resection. CA19-9 prior to primary resection, R status of first liver resection and median time to recurrence were significant determinants of repeated resectability. Median OS in the repeated resection group was 65.2 months, with consecutive 1-, 3- and 5-year OS of 98%, 78% and 57% respectively. After re-exploration, median OS from primary resection was 46.7 months, with a consecutive 1-, 3- and 5-year OS of 95%, 55% and 22% respectively. From the day of repeated resection, the median OS was 36.8 months, with a consecutive 1-, 3- and 5-year OS of 86%, 51% and 34% respectively. Minor morbidity (grade I+II) was present in 27%, grade IIIa-IVb morbidity in 20% and mortality in 3.5% of patients. Conclusion Repeated resection of ICC has acceptable morbidity and mortality and seems to be associated with improved long-term survival. Structured follow-up after resection of ICC is necessary for early identification of these patients.
Online veröffentlicht am 30 September 2020
Gesehen am 06.07.2021